“Estandarización de los procedimientos para el faenamiento de ganado ovino y porcino en el camal municipal del cantón Colta”. - Yumisaca Soque, Jorge Daniel (2017)
The present investigation of a necessity of the Camal Municipal of the Canton Colta and the exigencies of the markets and the awareness of the rights by the part of the consumers, compel the Camal Ecological Municipal dedicated to the animal slaughter to face scenarios each day more competitive ; At the same time, governments through their regulatory services raise new regulations aimed at reducing the health risks of those who consume food, for these reasons the Municipal Camal provides the service of slaughter of the different species of food, pork, sheep And goats under strict hygiene and sanitary inspection standards to provide the consumer with a product fit for human consumption, and goes hand in hand the demand for production of these products so it is necessary to optimize the processes of slaughter to increase productivity and be competitive . The main objective of this work is the standardization of procedures for sheep and pigs in the Municipal Camal of Canton Colta, using methods engineering to improve the processes. The calculation of the standard times for the two lines of fishing the next; The process of slaughtering a pig lives with a standard of time of 17.26 minutes, while the process of consolidation of a sheep takes a standard time of 11.41 minutes. Finally, the elaboration of the procedure (Annex 5) and The two working instructors (Annexes 6 and 7) to guide the operators in the execution of their activities in an efficient way. This research highlights the importance of determining the standard time, because thanks to companies have full knowledge of their capabilities and production limitations, thus achieving better decision making with both suppliers and customers.